Prospero's America : John Winthrop, Jr., alchemy, and the creation of New England culture, 1606-1676 - Woodward, Walter William (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 2010)
John Winthrop, Jr. participated in a pan-European network of natural philosophers who believed alchemy could improve the human condition and hasten Christ's Second Coming. Walter Woodward demonstrates how Winthrop and his philosophy influenced New England's cultural formation: its settlement, economy, religious toleration, Pequot Indian relations, medical practice, witchcraft prosecution, and imperial diplomacy. Prospero's America reconceptualizes the significance of early modern science in shaping New England hand in hand with Puritanism and politics.